2014
DOI: 10.1111/his.12317
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic utility of molecular and cytogenetic analysis in lipoblastoma: a study of two cases and review of the literature

Abstract: This report illustrates two different tumorigenic pathways implicating PLAG1 in lipoblastoma: amplification through multiple copies of a small marker chromosome derived from chromosome 8, and a paracentric inversion of the long arm of chromosome 8. Both these anomalies induced aberrant expression of PLAG1, emphasizing the role of PLAG1 in tumorigenesis. The aberrant expression of PLAG1 protein has been hypothesized, but this is the first report to demonstrate its occurrence in lipoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Close follow up for minimum of 5 years is recommended. Various studies have not reported any recurrences in completely excised tumors with follow ups of 2 months–10 years and median follow up times ranging from 38 to 42 months [ 11 , 14 , 15 , 19 , 22 , 24 , 25 , 27 , 30 ].…”
Section: Main Textmentioning
confidence: 99%
“…Close follow up for minimum of 5 years is recommended. Various studies have not reported any recurrences in completely excised tumors with follow ups of 2 months–10 years and median follow up times ranging from 38 to 42 months [ 11 , 14 , 15 , 19 , 22 , 24 , 25 , 27 , 30 ].…”
Section: Main Textmentioning
confidence: 99%
“…Given the importance of the diagnosis of liposarcoma, if doubts persist, it is necessary to perform an immunohistochemical and specific cytogenetic study to confirm the differences. [ 1 4 6 10 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in myxoid liposarcoma, translocation t(12;16) (q13;p11) and FUS-DDIT3 gene fusion are characteristic in 95% of cases. [ 1 11 22 25 ] The presence of p16, useful for the diagnosis of liposarcomas, is highlighted in an immunohistochemical study. [ 25 ] With a well-founded suspected diagnosis, treatment consisting of complete but nonmutilating excision with free margins can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 70 % of lipoblastomas exhibit PLAG1 rearrangement located at 8q12, which can result in the transcriptional upregulation of this oncogene via promoter swapping [ 9 , 10 ]. In addition, lipoblastoma demonstrates polysomy for chromosome 8 with or without PLAG1 rearrangement [ 9 , 10 , 12 , 13 ]. The detection of PLAG1 rearrangement is used to distinguish lipoblastoma from other lipomatous tumors as well as liposarcoma [ 2 , 3 , 7 , 8 , 10 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%